Presupposisi Pada Spanduk Gerobak Pedagang Kaki Lima di Kota Gorontalo (Kajian Pragmatik): Penelitian - Sri Rahmawati Pikoli; Mohamad Karmin Baruadi; Asna Ntelu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine and describe the form of use, types, and functions of presupposition in street vendor cart banners and the influence of presupposition on street vendor consumers in Gorontalo City. This research method is a descriptive method with a pragmatic approach based on the presupposition theory by Yule with a qualitative research type. Data collection techniques used in this study are observation, documentation, interviews, and notes. The results of the study show that (1) the form of use of presupposition is obtained from the principle of economy with 2 identified data; (2) there are 6 types of presupposition, namely existential, factive, lexical, structural, non-factive, and counterfactual presupposition with 1 data found for each; (3) there are 5 types of presupposition functions, including referential function, directive function, phatic function, metalingual function, and imaginative function with 1 data found for each; (4) consumer influence is based on 5 factors including the factor of using aesthetic words/phrases that attract attention, the factor of consumer curiosity (curiosity), the factor of using regional language/dialect that is easy to understand, the factor of liking & wanting the product, and the factor of clarity of the size of the writing on the banner, each of which has 1 data found.